Prophecy: Using history for high-throughput fault tolerance - Sen, Siddhartha; Lloyd, Wyatt; Freedman, Michael (Proc. 7th Networked Systems Design and Implementation (NSDI), 2010)
Byzantine fault-tolerant (BFT) replication has enjoyed a series of performance improvements, but remains costly due to its replicated work. We eliminate this cost for read-mostly workloads through Prophecy, a system that interposes itself between clients and any replicated service. At Prophecy’s core is a trusted sketcher component, designed to extend the semi-trusted load balancer that mediates access to an Internet service. The sketcher performs fast, load-balanced reads when results are historically consistent, and slow, replicated reads otherwise. Despite its simplicity, Prophecy provides a new form of consistency called delay-once consistency. Along the way, we derive a distributed variant of Prophecy that achieves the same consistency but without any trusted components. A prototype implementation demonstrates Prophecy’s high throughput compared to BFT systems. We also describe and evaluate Prophecy’s ability to scale-out to support large replica groups or multiple replica groups. As Prophecy is most effective when state updates are rare, we finally present a measurement study of popular websites that demonstrates a large proportion of static data.
16 pages